2022
DOI: 10.3390/ijerph19073903
|View full text |Cite
|
Sign up to set email alerts
|

Cybervictimization and Depression among Adolescents: Coping Strategies as Mediators

Abstract: Studies have shown the relationships among cybervictimization, coping strategies, and depression, but no study has examined the mechanism that links the three variables. Accordingly, this study used the transactional model of stress and coping theory as a conceptual framework and proposed that coping strategies are mediators for the effects of cybervictimization on depression. A total of 387 adolescents were recruited by using the purposive sampling method. The results showed that cybervictimization is not dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…In particular, when emotion get the better of rational judgment, they may be barred from utilizing effective coping strategies (eg, referring to adults when problems get out of hand) or may be inclined to choose self-destructive strategies (such as substance misuse, escapism, or avoidant strategies). 24,34 Coping strategies are As observed in the interaction model, positive core belief predicted lower affective symptoms. It also displayed a trend toward negative interaction with cyberbullying victimization, meaning that the effects of cyberbullying victimization on affective symptoms decreased as the rating of positive core belief increased.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…In particular, when emotion get the better of rational judgment, they may be barred from utilizing effective coping strategies (eg, referring to adults when problems get out of hand) or may be inclined to choose self-destructive strategies (such as substance misuse, escapism, or avoidant strategies). 24,34 Coping strategies are As observed in the interaction model, positive core belief predicted lower affective symptoms. It also displayed a trend toward negative interaction with cyberbullying victimization, meaning that the effects of cyberbullying victimization on affective symptoms decreased as the rating of positive core belief increased.…”
Section: Discussionmentioning
confidence: 58%
“…In particular, when emotion get the better of rational judgment, they may be barred from utilizing effective coping strategies (eg, referring to adults when problems get out of hand) or may be inclined to choose self-destructive strategies (such as substance misuse, escapism, or avoidant strategies). 24 , 34 Coping strategies are therefore potential targets for specific interventions. Additionally, addressing resilience features would help buffer the impact on mental health.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, some studies have suggested that cyberbullying coping behaviors are mediators for the effects of cyber-victimization on certain psychological outcomes. For example, Jose and Vierling (2018) reported that coping with rumination mediates the effects of cyber-victimization on sleep proficiency, and Zhou et al (2022) determined that awareness-raising and social support strategies mediate the effects of cybervictimization on suicidal thoughts. Based on previous research, this study hypothesized that cyber victimization is associated with cyberbullying coping behaviors.…”
Section: The Mediator Role Of Behaviors In Coping With Cyberbullyingmentioning
confidence: 99%
“…The victims report more frequent health, emotional, and school-related problems together with poorer relationships with classmates in comparation with those who have not been exposed to bullying [16,17]. Furthermore, cybervictims are more likely to be adolescents who have a poor relationship with their parents [18]. The school-related problems can be reflected in lower grades, missing or disliking school, peer relationship problems, suspension, etc.…”
Section: Introductionmentioning
confidence: 99%